Evaluation of trade-offs in traditional methodologies for measuring metazooplankton growth rates: Assumptions, advantages and disadvantages for field applications. (November 2019) - Kobari, Toru; Sastri, Akash R.; Yebra, Lidia; Liu, Hui; Hopcroft, Russell R.
Highlights: Traditional approaches to measure mesozooplankton growth in nature are reviewed. Each method involves trade-offs among the advantages, disadvantages and limitations. Comparison and validation of the estimates with several methods are recommended. Abstract: Zooplankton growth rates ultimately shape the functional response of marine ecosystems to regional and global climate changes, because they determine the quantity and distribution of matter and energy within the zooplankton community available to higher trophic levels. Despite the variety of techniques available for measuring zooplankton growth, no or few approaches have been universally applied to the natural zooplankton populations or community and there are only a limited number of comparisons among the methods. Here we review and compile data for the traditional methods for estimating metazooplankton weight-specific growth rates, describe the principles and underlying assumptions of each method, and finally their advantages and disadvantages. This review encompasses the analysis of time-series (i.e., Natural Cohort method), three experimental approaches (i.e., Artificial Cohort, Molting Rate and Egg Production) and several empirical models that have been applied to specific stages, populations or community guilds of metazooplankton in the field. Whereas, some methodological problems and their resolution have been proposed in the past, no single method adequately addresses the high biodiversity of metazooplankton communities and resolves our limited capacity determining rates. We recommend a more formal comparison of methodologies be undertaken that would allow for their direct cross-calibration to facilitate future cross-site synthesis.